Plan maestro: rehabilitación y conectividad del Rio Magdalena Medio - plan parcial: centralidad de desarrollo fluvial agroindustrial - proyecto arquitectónico: Jardín del Eden - centro de producción y distribución de cultivos hidropónicos (2020)
In the intervention sector that runs from the south of Cesar to the North of Santander, different variables or problems were identified, such as agricultural monopolization and environmental pollution given by oil refineries in this sector, additionally the possibility of navigability and transport along the Magdalena River was found. With this you can come from defining different models of change or helping the sector through architectural design. The development of a master plan sectorizing and improving the intervention area, by identifying an agro-industrial development area in Barrancabermeja. The development of this as a partial plan would create the possibility of mitigation in the development and improvement of the connection along the Magdalena river, in addition the development would generate jobs in the sector and expand the agricultural field.